Cereblon-Based Small-Molecule Compounds to Control Neural Stem Cell Proliferation in Regenerative Medicine - Sato, Tomomi; Ito, Takumi; Handa, Hiroshi (Frontiers in Cell and Developmental Biology, 2021)
Thalidomide, a sedative drug that was once excluded from the market owing to teratogenic activities, was found to be effective for the treatment of multiple myeloma. We previously demonstrated that cereblon (CRBN) is the target of thalidomide embryopathy and acts as a substrate receptor of the E3 ubiquitin ligase complex, Cullin-Ring ligase 4 (CRL4CRBN) in zebrafish and chicks. CRBN was originally identified as a gene responsible for mild intellectual disability in humans. Fetuses exposed to thalidomide in early pregnancy were at risk for neurodevelopmental disorders such as autism, suggesting that CRBN is involved in prenatal brain development. Recently, we found that CRBN controls the proliferation of neural stem cells in the developing zebrafish brain, leading to changes in brain size. Our findings imply that CRBN is involved in neural stem cell growth in humans. Accumulating evidence shows that CRBN is essential not only for the teratogenic effects but also for the therapeutic effects of thalidomide. This review summarizes recent progress in thalidomide and CRBN research, focusing on the teratogenic and therapeutic effects. Investigation of the molecular mechanisms underlying the therapeutic effects of thalidomide and its derivatives, CRBN E3 ligase modulators (CELMoDs), reveals that these modulators provide CRBN the ability to recognize neosubstrates depending on their structure. Understanding the therapeutic effects leads to the development of a novel technology called CRBN-based proteolysis-targeting chimeras (PROTACs) for target protein knockdown. These studies raise the possibility that CRBN-based small-molecule compounds regulating proliferation of neural stem cells may be developed for application in regenerative medicine.